Keberagaman dan Toleransi: Pandangan Islam dan Penerapannya dalam Masyarakat Tongkonan Rannu - Puspa Sari, Herma; Rafeyfa Asyla, Alya; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
Religious diversity is an unavoidable social reality in a pluralistic society. In the Islamic perspective, diversity is God's will (sunnatullah) that requires humans to live in peace and recognise each other. This research raises the issue of Islamic views on ethnic, racial, religious, and cultural differences in Tongkonan Rannu, as well as the application of Islamic values in promoting tolerance and social harmony. The purpose is to analyse the Islamic view of diversity and examine the application of its values in the life of a pluralistic society. The method used is descriptive qualitative with observation and interview techniques. The results showed that Islam upholds tolerance (tasamuh), justice, and religious freedom. In Tongkonan Rannu, Muslims live in harmony with other groups through mutual respect and cooperation. The inclusive values of Islam are key to realising a peaceful, harmonious, and tolerant society amidst diversity.